Copepod Life Strategy and Population Viability in Response to Prey Timing and Temperature: Testing a New Model across Latitude, Time, and the Size Spectrum - Banas, Neil S.; Møller, Eva F.; Nielsen, Torkel G.; Eisner, Lisa B. (Frontiers in Marine Science, 2016)
A new model ("Coltrane": Copepod Life-history Traits and Adaptation to Novel Environments) describes environmental controls on copepod populations via 1) phenology and life history and 2) temperature and energy budgets in a unified framework. The model tracks a cohort of copepods spawned on a given date using a set of coupled equations for structural and reserve biomass, developmental stage, and survivorship, similar to many other individual-based models. It then analyzes a family of cases varying spawning date over the year to produce population-level results, and families of cases varying one or more traits to produce community-level results. In an idealized global-scale testbed, the model correctly predicts life strategies in large Calanus spp. ranging from multiple generations per year to multiple years per generation. In a Bering Sea testbed, the model replicates the dramatic variability in the abundance of C. glacialis/marshallae observed between warm and cold years of the 2000s, and indicates that prey phenology linked to sea ice is a more important driver than temperature per se. In a Disko Bay, West Greenland testbed, the model predicts the viability of a spectrum of large-copepod strategies from income breeders with a adult size ~100 µgC reproducing once per year through capital breeders with an adult size >1000 µgC with a multiple-year life cycle. This spectrum corresponds closely to the observed life histories and physiology of local populations of C. finmarchicus, C. glacialis, and C. hyperboreus. Together, these complementary initial experiments demonstrate that many patterns in copepod community composition and productivity can be predicted from only a few key constraints on the individual energy budget: the total energy available in a given environment per year; the energy and time required to build an adult body; the metabolic and predation penalties for taking too long to reproduce; and the size and temperature dependence of the vital rates involved.